2022
DOI: 10.2147/cmar.s347323
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Immunological Level Determined the Prognosis of Leptomeningeal Metastasis in Lung Cancer

Abstract: Background and Purpose Leptomeningeal metastases (LM) is the end-event of lung cancer and the prognosis is dismal. Few studies explored the prognostic performance of systematic immunological levels in lung cancer patients with LM. Our study aimed to explore the possible relationship between the prognosis of LM and systematic immunological level and other clinical characteristics. Methods This retrospective, multi-institutional, observational study was conducted in 4 ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
4
7
0
Order By: Relevance
“…3 d). This result was consistent with our previous work, indicating that PM might be a risk factor for LM 18 . Although the mechanism beneath remained elusive, we reasonably inferred cancer cells evolved to acquire additional capabilities to accustomed to the hypoxic leptomeningeal compartment.…”
Section: Discussionsupporting
confidence: 94%
“…3 d). This result was consistent with our previous work, indicating that PM might be a risk factor for LM 18 . Although the mechanism beneath remained elusive, we reasonably inferred cancer cells evolved to acquire additional capabilities to accustomed to the hypoxic leptomeningeal compartment.…”
Section: Discussionsupporting
confidence: 94%
“…3d). This result was consistent with our previous work, indicating that PM might be a risk factor for LM [17]. Although the mechanism beneath remained elusive, we reasonably inferred cancer cells evolved to acquire additional capabilities to accustomed to the hypoxic leptomeningeal compartment.…”
Section: Discussionsupporting
confidence: 93%
“…Younger age, EGFR L858R, no pleural metastases, adrenal gland metastases and elevated CEA were risk factors. Of notice, some factors were referenced in other studies as well, which might suggest the reliability of our model [17,19,20]. Our model was a comprehensive one, including factors from clinical (age and metastases) to laboratory ndings (EGFR mutation and tumor markers).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Eleven studies (23,24,(29)(30)(31)(32)(33)(34)(35)(36)(37) reported the association of NLR and OS in lung cancer patients with BM. The random effects model was applied because the test for heterogeneity showed signi cant heterogeneity among the included studies (P = 0.016, I 2 = 54.0%).…”
Section: Results Of Meta-analysismentioning
confidence: 99%